Secondary battery and electronic device

CN122996511APending Publication Date: 2026-10-27NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580003019.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

Inconsistent capacity between individual secondary battery cells leads to rapid capacity decay and short lifespan, posing safety hazards.

Method used

By controlling the particle size distribution of the positive electrode active material and the content of sulfur-oxygen double bond compounds and nitrile compounds in the electrolyte, a protective film is formed to suppress side reactions and improve the interfacial stability between the positive electrode and the electrolyte.

Benefits of technology

It effectively suppressed heterogeneous reactions, improved the capacity consistency between secondary battery cells, extended battery life, and reduced safety hazards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A secondary battery and an electronic device, the secondary battery comprising a positive electrode sheet and an electrolyte, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, a particle size Dv10 of the positive electrode active material being D1 μm, a particle size Dv90 of the positive electrode active material being D2 μm, 1.2 ≤ D2 / D1 ≤ 6.6, 2.9 ≤ D2 ≤ 7.8; the electrolyte comprising at least one of a sulfur-oxygen double bond compound or a nitrile compound, a mass percentage content of the sulfur-oxygen double bond compound and the nitrile compound based on a mass of the electrolyte being W1%, 0.5 ≤ W1 ≤ 7; D2 and W1 satisfying: 1.5 ≤ W1 × D2 ≤ 30.
Need to check novelty before this filing date? Find Prior Art

Description

Secondary batteries and electronic devices Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a secondary battery and electronic device. Background Technology

[0002] Secondary batteries, such as lithium-ion batteries, are widely used in smartphones, wearable devices, consumer drones, and electric vehicles due to their advantages such as high energy density, long cycle life, and no memory effect. However, when multiple secondary battery cells are connected in series or parallel, the secondary battery may experience rapid capacity decay and short lifespan due to inconsistencies between the cells. Furthermore, individual cells may overcharge or over-discharge, posing serious safety hazards. Therefore, improving the capacity consistency between different cells in a secondary battery has become a pressing technical problem for those skilled in the art. Summary of the Invention

[0003] The purpose of this application is to provide a secondary battery and an electronic device to improve the capacity consistency between different cells of the secondary battery.

[0004] It should be noted that while this application uses lithium-ion batteries as an example of secondary batteries to explain the invention, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0005] The first aspect of this application provides a secondary battery, which includes a positive electrode and an electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer includes a positive active material with a particle size Dv10 of D1 μm and a particle size Dv90 of D2 μm, wherein 1.2 ≤ D2 / D1 ≤ 6.6 and 2.9 ≤ D2 ≤ 7.8. The electrolyte includes at least one of a sulfur-oxygen double bond compound or a nitrile compound. Based on the mass of the electrolyte, the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is W1%, wherein 0.5 ≤ W1 ≤ 7. D2 and W1 satisfy: 1.5 ≤ D2 × W1 ≤ 30. The secondary battery provided in the first aspect of this application reduces the overall size of the positive electrode active material particles by controlling the particle size Dv90 within the range specified in this application. Furthermore, by controlling the ratio D2 / D1 of the particle size Dv90 to Dv10 of the positive electrode active material within the range specified in this application, the uniformity of the particle size distribution of the positive electrode active material particles can be improved. This suppresses the problem of inconsistent capacity decay caused by heterogeneous reactions. Sulfur-oxygen double bond compounds and nitrile compounds can synergistically improve the interface conditions on the positive electrode side, suppressing side reactions between the positive electrode and the electrolyte. By controlling the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds, and ensuring that the value of the relationship between the particle size Dv90 of the positive electrode active material and the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds (D2×W1) is within the aforementioned range, this application can enhance the film protection on the surface of the positive electrode, suppress the occurrence of side reactions on the positive electrode side, thereby reducing the degree of capacity decay of the secondary battery and improving the capacity consistency between different secondary battery cells. Therefore, by adjusting D2 / D1, D2, W1, and D2×W1 to fall within the scope of this application, the capacity consistency between different cells in a secondary battery can be improved.

[0006] In one embodiment of this application, 0.9 ≤ D1 ≤ 4.8. Controlling the particle size Dv10 of the positive electrode active material within the above range is beneficial for the positive electrode active material particles to have a smaller particle size, thereby helping to suppress the problem of capacity decay uniformity caused by heterogeneous reactions.

[0007] In one embodiment of this application, the secondary battery satisfies at least one of the following characteristics: (1) 2≤D2 / D1≤5; (2) 3.5≤D2≤7; (3) 2≤W1≤6; (4) 8≤D2×W1≤25; (5) 1≤D1≤3.

[0008] In one embodiment of this application, the mass percentage of the sulfur-oxygen double bond compound is W, based on the mass of the electrolyte. 11 %, the mass percentage of nitrile compounds is W 12 %, 0.5≤W 11≤6, 0.1≤W 12 ≤3. Controlling the mass percentage of sulfur-oxygen double bond compounds and nitrile compounds in the electrolyte within the above range is beneficial to reducing the degree of capacity decay and improving the capacity consistency between different cells in the secondary battery.

[0009] In one embodiment of this application, the secondary battery satisfies at least one of the following characteristics: (i) 1.5 ≤ W 11 ≤4.2; (ii)0.3≤W 12 ≤2.1.

[0010] In one embodiment of this application, the sulfur-oxygen double bond compound includes at least one selected from 1,3-propanesulfonate, vinyl sulfate, propenesulfonate lactone, 3-fluoro-1,3-propanesulfonate lactone, 1,2-propanesulfonate lactone, 1,4-butanesulfonate lactone, 1,2-butanesulfonate lactone, 1,3-butanesulfonate lactone, 2,4-butanesulfonate lactone, or 1,3-pentanesulfonate lactone. Using the above-mentioned sulfur-oxygen double bond compounds in the electrolyte is beneficial for reducing the capacity decay of the secondary battery and improving the capacity consistency between different cells in the secondary battery.

[0011] In one embodiment of this application, the nitrile compound includes at least one selected from malononitrile, butadionitrile, glutaronitrile, adiponitrile, heptanonitrile, octadionitrile, 3,3'-oxodipropionitrile, hex-2-enadionitrile, trans-butenedionitrile, 2-pentenedionitrile, methylglutaronitrile, 4-cyanohepanitrilon, (Z)-but-2-enadionitrile, 2,2,3,3-tetrafluorobutadionitrile, ethylene glycol bis(propionitrile) ether, 4-cyanohepanitrilon, 4-(2-cyanoethyl)heptanedionitrile, or 1,2,3-tris-(2-cyanoethoxy)propane, 1,4-dicyano-2-butene, 1,3,6-hexanetrionitrile, or 1,2,3-tris(2-cyanoxy)propane. Using the above-mentioned sulfur-oxygen double bond compounds in the electrolyte is beneficial for reducing the capacity decay of the secondary battery and improving the capacity consistency between different cells in the secondary battery.

[0012] In one embodiment of this application, the sulfur-oxygen double bond compound includes at least one selected from 1,3-propanesulfonyl lactone, propenesulfonate lactone, or 2,4-butanesulfonate lactone; and / or, the nitrile compound includes at least one selected from adiponitrile, succinic anhydride, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrionitrile, or 1,2,3-tris(2-cyanoxy)propane or 1,4-dicyano-2-butene. Using the above-mentioned sulfur-oxygen double bond compounds and / or nitrile compounds in the electrolyte is beneficial for further reducing the capacity decay of the secondary battery and improving the capacity consistency between different cells in the secondary battery.

[0013] In one embodiment of this application, the positive electrode active material is a nickel-cobalt-manganese ternary material. Based on the total molar amount of nickel, cobalt, and manganese, the molar content of nickel is M3%, where M3 ≥ 50. The positive electrode active material also includes other doping elements, which include at least one of Al, Ta, Zr, B, Ti, or Y. Based on the total mass of nickel, cobalt, and manganese, the mass percentage of other doping elements is W4%, where 0 ≤ W4 < 10. Controlling the content and type of nickel and other doping elements in the positive electrode active material within the above range is beneficial for improving the capacity consistency of different cells in the secondary battery, thereby enabling the secondary battery to have higher energy density and cycle performance.

[0014] A second aspect of this application provides an electronic device comprising the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device exhibits good performance.

[0015] The beneficial effects of this application are:

[0016] This application provides a secondary battery and an electronic device. The secondary battery includes a positive electrode and an electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer includes a positive active material with a particle size Dv10 of D1 μm and a particle size Dv90 of D2 μm, wherein 1.2 ≤ D2 / D1 ≤ 6.6 and 2.9 ≤ D2 ≤ 7.8. The electrolyte includes at least one of a sulfur-oxygen double bond compound or a nitrile compound. Based on the mass of the electrolyte, the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is W1%, wherein 0.5 ≤ W1 ≤ 7. D2 and W1 satisfy: 1.5 ≤ W1 × D2 ≤ 30. Through the above configuration, the capacity consistency between different cells of the secondary battery can be improved. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of this application clearer, the following embodiments are provided to further illustrate this application in detail. Obviously, the described embodiments are merely some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0018] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries in this application are not limited to lithium-ion batteries.

[0019] The first aspect of this application provides a secondary battery, comprising a positive electrode and an electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The aforementioned "positive active material layer disposed on at least one surface of the positive current collector" means that the positive active material layer can be disposed on one or both surfaces of the positive current collector, and the "surface" can be a partial or complete area of ​​the surface of the positive current collector. The positive active material layer includes a positive active material with a particle size Dv10 of D1 μm and a particle size Dv90 of D2 μm, wherein 1.2 ≤ D2 / D1 ≤ 6.6 and 2.9 ≤ D2 ≤ 7.8. The electrolyte includes at least one of a sulfur-oxygen double bond compound or a nitrile compound. Based on the mass of the electrolyte, the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is W1%, wherein 0.5 ≤ W1 ≤ 7; D2 and W1 satisfy: 1.5 ≤ D2 × W1 ≤ 30.

[0020] For example, the value of D2 / D1 can be 1.2, 1.4, 1.6, 1.7, 2, 2.3, 2.5, 2.9, 3.0, 3.6, 3.9, 4.2, 4.4, 4.7, 5, 5.2, 5.4, 5.8, 6.2, 6.6, or any value within any two of the above ranges. A D2 / D1 value less than 1.2 places excessively high demands on the production process of the positive electrode active material, making it difficult to synthesize a satisfactory positive electrode active material. A D2 / D1 value greater than 6.6 indicates that the particle size Dv90 of the positive electrode active material is too large relative to the particle size Dv10, resulting in uneven particle size distribution and significant differences in particle size, which can easily lead to capacity decay in the secondary battery.

[0021] For example, D2 can be 2.9, 3.2, 3.5, 3.9, 4.3, 4.6, 4.9, 5.1, 5.6, 6.1, 6.5, 6.8, 7.1, 7.8, or any value within any two of the above ranges. If D2 is less than 2.9, the particle size Dv90 of the positive electrode active material is too small. This results in an excessively large specific surface area and excessive contact area with the electrolyte, leading to excessive side reactions, excessive electrolyte consumption, and significant gas and heat generation, negatively impacting the performance of the secondary battery, such as storage and safety. If D2 is greater than 7.8, the particle size Dv90 of the positive electrode active material is too large, reducing the number of active sites and the contact area between particles, thus affecting the activity of the positive electrode active material and increasing the thickness of the positive electrode active material layer, thereby affecting the performance of the secondary battery, such as energy density and cycle performance.

[0022] For example, W1 can be 0.5, 1, 1.5, 1.7, 1.9, 2.1, 2.6, 2.9, 3, 3.2, 3.5, 3.8, 4.2, 4.6, 4.8, 5.0, 5.4, 5.6, 5.8, 6.2, 6.8, 7, or any value within any two of the above ranges. If W1 is less than 0.5, the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds is too small, failing to protect the positive electrode active material; if W1 is greater than 7, the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds is too large, consuming too many lithium ions and leading to rapid capacity decay of the secondary battery.

[0023] For example, D2×W1 can be 1.5, 5, 7, 8, 10, 12, 15, 17, 20, 22, 24, 25, 26, 27, 30, or any value within any two of the above ranges. The smaller the particle size Dv90 of the positive electrode active material, the larger the specific surface area of ​​the positive electrode active material particles, the larger the contact area with the electrolyte, and the more side reactions with the electrolyte. This requires more sulfur-oxygen double bond compounds and nitrile compounds to protect the positive electrode active material and suppress side reactions, thereby improving the consistency of the secondary battery capacity. Conversely, the larger the particle size Dv90 of the positive electrode active material, the smaller the specific surface area of ​​the positive electrode active material particles, the fewer side reactions between the positive electrode active material and the electrolyte, and the less sulfur-oxygen double bond compounds and nitrile compounds are needed for the positive electrode active material. If D2×W1 is less than 1.5, it indicates that D2×W1 is too small, meaning the particle size Dv90 of the positive electrode active material and the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds are too small, insufficient to protect the positive electrode active material. If D2×W1 is greater than 30, it indicates that D2×W1 is too large, meaning the particle size Dv90 of the positive electrode active material is too large, or the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds is too large. If the particle size Dv90 of the positive electrode active material is too large, the number of active sites will decrease, the contact area between particles will decrease, affecting the activity performance of the positive electrode active material, and also increasing the thickness of the positive electrode active material layer, thus affecting the performance of the secondary battery (such as energy density and cycle performance). If the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds is too large, it will consume too many lithium ions, leading to rapid capacity decay of the secondary battery.

[0024] Heterogeneous reaction kinetics induce lattice distortion and rotation within individual positive electrode active material particles during secondary battery charging. During charge-discharge cycles, the accumulation of irreversible lattice rotation exacerbates morphological and structural damage, leading to capacity decay in the secondary battery. When different secondary battery cells are connected in series or parallel, the varying sizes of their positive electrode active material particles result in different degrees of capacity decay among the individual cells. The secondary battery provided in the first aspect of this application reduces the overall size of the positive electrode active material particles by controlling the particle size Dv90 within the range specified in this application. Furthermore, by controlling the ratio D2 / D1 of the particle sizes Dv90 to Dv10 within the range specified in this application, the uniformity of the particle size distribution of the positive electrode active material particles can be improved. This suppresses the problem of inconsistent capacity decay caused by heterogeneous reactions. Sulfide-oxygen double bond compounds and nitrile compounds can synergistically improve the interfacial condition on the positive electrode side, suppressing side reactions between the positive electrode and the electrolyte. This application enhances the film formation protection on the surface of the positive electrode by controlling the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds, and by ensuring that the relationship between the particle size Dv90 of the positive electrode active material and the sum of the mass percentages of sulfur-oxygen double bond compounds and nitrile compounds, D2×W1, is within the aforementioned range. This suppresses the occurrence of side reactions on the positive electrode, thereby reducing the capacity decay of the secondary battery and improving the capacity consistency between different secondary battery cells. Therefore, by controlling D2 / D1, D2, W1, and D2×W1 within the range of this application, the capacity consistency between different secondary battery cells can be improved.

[0025] In this application, "particle size Dv10 of the positive electrode active material" means that, in the particle size distribution based on volume, the particle size reaches 10% of the total volume from the smallest particle size side. "Particle size Dv90 of the positive electrode active material" means that, in the particle size distribution based on volume, the particle size reaches 90% of the total volume from the smallest particle size side.

[0026] This application does not impose any particular restrictions on the method of controlling the particle size of the positive electrode active material, as long as the purpose of this application can be achieved. For example, it can be achieved through crushing, sieving, or other methods.

[0027] In one embodiment of this application, 0.9 ≤ D1 ≤ 4.8. For example, D1 is 0.9, 1, 1.2, 1.4, 1.6, 1.7, 2, 2.3, 2.5, 2.9, 3.0, 3.6, 3.9, 4.2, 4.4, 4.8, or any value between any two of the above ranges. Controlling the particle size Dv10 of the positive electrode active material within the above range is beneficial for achieving a smaller particle size, thereby helping to suppress the problem of inconsistent capacity decay caused by heterogeneous reactions.

[0028] In one embodiment of this application, 2 ≤ D2 / D1 ≤ 5. For example, the value of D2 / D1 is 2, 2.3, 2.5, 2.6, 2.9, 3.0, 3.3, 3.6, 3.9, 4.2, 4.4, 4.7, 5, or any value between any two of the above ranges. By adjusting the value of D2 / D1 within the above range, the uniformity of the particle size distribution of the positive electrode active material can be further improved, thereby further suppressing the capacity decay uniformity problem caused by non-uniform reactions, and further improving the capacity uniformity between different cells in the secondary battery.

[0029] In one embodiment of this application, 3.5 ≤ D2 ≤ 7. For example, D2 is 3.5, 3.9, 4.3, 4.6, 4.9, 5.1, 5.6, 6.1, 6.5, 6.8, 7, or any value between any two of the above ranges. By controlling the particle size Dv90 of the positive electrode active material within the above range, the uniformity of the particle size distribution of the positive electrode active material can be further improved, thereby further suppressing the capacity decay inconsistency problem caused by non-uniform reactions, and further improving the capacity consistency between different cells in the secondary battery.

[0030] In one embodiment of this application, 2 ≤ W1 ≤ 6. For example, W1 is 2, 2.3, 2.8, 3, 3.3, 3.6, 4, 4.2, 4.7, 5, 5.3, 5.6, 6, or any value within any two of the above ranges. Controlling the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound within the above range is beneficial in reducing the probability of the sulfur-oxygen double bond compound and the nitrile compound consuming more lithium ions while protecting the positive electrode active material. The synergistic effect of the sulfur-oxygen double bond compound and the nitrile compound improves the positive electrode interface and suppresses side reactions between the positive electrode sheet and the electrolyte, thereby improving the capacity consistency between different cells in the secondary battery.

[0031] In one embodiment of this application, 8 ≤ D2×W1 ≤ 25. For example, D2×W1 is 8, 10, 12, 15, 17, 20, 22, 24, 25, or any value between any two of the above ranges. Controlling the value of D2×W1 within the above range is beneficial for ensuring that the positive electrode active material particles have a suitable size, that sulfur-oxygen double bond compounds and nitrile compounds have appropriate contents in the electrolyte, and that the positive electrode active material is well protected. This reduces the probability of side reactions between the positive electrode active material and the electrolyte, thereby reducing the degree of capacity decay and improving the capacity consistency between different cells in the secondary battery.

[0032] In one embodiment of this application, 1 ≤ D1 ≤ 3. For example, D1 is 1, 1.2, 1.4, 1.6, 1.7, 2, 2.3, 2.5, 2.9, 3.0, or any value between any two of the above ranges. Controlling the particle size Dv10 of the positive electrode active material within the above range helps to reduce the probability of agglomeration of the positive electrode active material particles during the preparation of the positive electrode slurry, thereby further suppressing the problem of inconsistent capacity decay caused by heterogeneous reactions.

[0033] In one embodiment of this application, the mass percentage of the sulfur-oxygen double bond compound is W, based on the mass of the electrolyte. 11 %, the mass percentage of nitrile compounds is W 12 %, 0.5≤W 11 ≤6, 0.1≤W 12 ≤3. For example, W 11 The value is 0.5, 1, 1.2, 1.5, 1.9, 2.2, 2.4, 2.6, 2.9, 3.1, 3.5, 3.7, 4.0, 4.2, 4.6, 4.8, 5.0, 5.2, 5.3, 5.7, 6, or any value between any two of the above ranges. 12 The values ​​are 0.1, 0.4, 0.7, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2.2, 2.4, 2.6, 2.7, 3, or any value within any two of the above ranges. Sulfur-oxygen double bond compounds possess positive electrode film-forming properties, while nitrile compounds have the property of adsorbing onto the surface of the positive electrode active material and masking its active sites. Controlling the mass percentage of sulfur-oxygen double bond compounds and nitrile compounds in the electrolyte within the above ranges provides good protection for the positive electrode active material, reduces the probability of side reactions between the positive electrode active material and the electrolyte, thereby reducing capacity decay and improving the capacity consistency between different cells in the secondary battery.

[0034] In one embodiment of this application, 1.5 ≤ W 11 ≤4.2. For example, W 11 The values ​​are 1.5, 1.9, 2.2, 2.4, 2.6, 2.9, 3.1, 3.5, 3.7, 4.0, 4.2, or any value within any two of the above ranges. Controlling the mass percentage of sulfur-oxygen double bond compounds in the electrolyte within these ranges is beneficial for forming a dense protective film on the surface of the positive electrode, reducing the probability of side reactions between the positive electrode active material and the electrolyte, thereby reducing capacity decay and further improving the capacity consistency between different cells in the secondary battery.

[0035] In one embodiment of this application, 0.3 ≤ W 12 ≤2.1. For example, W12 The value can be 0.3, 0.4, 0.7, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2.1, or any value within any two of the above ranges. Controlling the mass percentage of nitrile compounds in the electrolyte within these ranges helps to mask the active sites on the surface of the positive electrode active material, thereby reducing the probability of side reactions between the positive electrode active material and the electrolyte. This further reduces the capacity decay of the secondary battery, thus improving the capacity consistency between different cells in the secondary battery.

[0036] In one embodiment of this application, the sulfur-oxygen double bond compound includes at least one selected from 1,3-propanesulfonyl lactone, vinyl sulfate, propenesulfonyl lactone, 3-fluoro-1,3-propanesulfonyl lactone, 1,2-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, 1,2-butanesulfonyl lactone, 1,3-butanesulfonyl lactone, 2,4-butanesulfonyl lactone, or 1,3-pentanesulfonyl lactone. Using the above-mentioned sulfur-oxygen double bond compounds in the electrolyte is beneficial for forming a dense protective film on the surface of the positive electrode, reducing the probability of side reactions between the positive electrode and the electrolyte, reducing the capacity decay of the secondary battery, and improving the capacity consistency between different cells in the secondary battery.

[0037] In one embodiment of this application, the nitrile compound includes at least one selected from malononitrile, butadionitrile, glutaronitrile, adiponitrile, heptanonitrile, octadionitrile, 3,3'-oxodipropionitrile, hex-2-enadionitrile, trans-butenedionitrile, 2-pentenedionitrile, methylglutaronitrile, 4-cyanohepanitrile, (Z)-but-2-enadionitrile, 2,2,3,3-tetrafluorobutadionitrile, ethylene glycol bis(propionitrile) ether, 4-cyanohepanitrile, 4-(2-cyanoethyl)heptanedionitrile or 1,2,3-tris-(2-cyanoethoxy)propane, 1,4-dicyano-2-butene, 1,3,6-hexanetrionitrile or 1,2,3-tris(2-cyanoxy)propane. Using the above-mentioned nitrile compounds in the electrolyte can reduce the number of active sites on the surface of the positive electrode active material, reduce the probability of side reactions between the positive electrode and the electrolyte, reduce the capacity decay of the secondary battery, and improve the capacity consistency between different cells of the secondary battery.

[0038] In one embodiment of this application, the sulfur-oxygen double bond compound includes at least one selected from 1,3-propanesulfonyl lactone, propenesulfonyl lactone, or 2,4-butanesulfonyl lactone; and / or, the nitrile compound includes at least one selected from adiponitrile, succinic anhydride, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrionitrile, or 1,2,3-tris(2-cyanoxy)propane or 1,4-dicyano-2-butene. Using the above-mentioned sulfur-oxygen double bond compounds and / or nitrile compounds in the electrolyte is beneficial for forming a denser protective film on the surface of the positive electrode, resulting in fewer active sites on the surface of the positive electrode active material. This further reduces the probability of side reactions between the positive electrode and the electrolyte, thereby further reducing the capacity decay of the secondary battery and improving the capacity consistency between different cells in the secondary battery.

[0039] In one embodiment of this application, the electrolyte further includes an organic solvent and a lithium salt. This application does not particularly limit the types of organic solvents and lithium salts; those skilled in the art can select organic solvents and lithium salts known in the art according to actual needs, as long as the purpose of this application can be achieved. For example, the organic solvent includes, but is not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents. The aforementioned carbonate compounds may be at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorinated carbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (MEC). Cyclic carbonate compounds may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), or vinyl ethylene carbonate (VEC). Fluorocarbonate compounds may include, but are not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. Other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, or phosphate esters. Lithium salts include, but are not limited to, at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate-borate), or lithium di(fluorooxalate-borate). This application does not impose any particular limitation on the content of organic solvents and lithium salts, as long as the purpose of this application is achieved. For example, based on the mass of the electrolyte, the organic solvent content is 77% to 91.5% by mass, and the lithium salt content is 8% to 16% by mass.

[0040] In one embodiment of this application, the positive electrode active material is a nickel-cobalt-manganese ternary material. Based on the total molar amount of nickel, cobalt, and manganese, the molar content of nickel is M3%, where M3 ≥ 50; further, 50 ≤ M3 ≤ 99. The positive electrode active material also includes other doping elements, including at least one of Al, Ta, Zr, B, Ti, or Y. Based on the total mass of nickel, cobalt, and manganese, the mass percentage of other doping elements is W4%, where 0 ≤ W4 < 10. For example, W4 is 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 9.9, or any value between any two of the above ranges. Nickel-cobalt-manganese ternary materials with nickel content and the content and types of other doping elements within the above ranges have high capacity and good structural stability. Using them as positive electrode active materials is beneficial for improving the capacity consistency of different cells in the secondary battery, thereby enabling the secondary battery to have a higher energy density.

[0041] This application does not impose any particular restrictions on the method of controlling the content of other doped and coated elements in the positive electrode active material, as long as the purpose of this application can be achieved. For example, it can be achieved by controlling the raw material ratio, temperature, etc.

[0042] In one embodiment of this application, the nickel-cobalt-manganese ternary material includes LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.71 Co 0.14 Mn 0.15 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.91 Co 0.04 Mn 0.05 O2, LiNi 0.92 Co 0.03 Mn 0.05 O2, LiNi 0.93 Co 0.02 Mn 0.05 O2, LiNi 0.94 Co 0.01 Mn 0.05 O2, LiNi 0.95 Co 0.01 Mn0.04 O2 or LiNi 0.8 Co 0.1 Mn 0.1 At least one of O2.

[0043] This application does not impose any particular restrictions on the preparation method of positive electrode active materials containing other doped coating elements, as long as the purpose of this application can be achieved. For example, the preparation method of positive electrode active materials containing other doped coating elements includes, but is not limited to, the following steps: (1) preparing a hydroxide precursor containing Ni, Co, and Mn elements by hydrothermal method; (2) thoroughly mixing the prepared hydroxide precursor with a lithium source and a dopant compound, and then sintering at high temperature to obtain a positive electrode active material containing other doped coating elements. This application does not impose any particular restrictions on the type of hydroxide precursor mentioned above, as long as the purpose of this application can be achieved. For example, the hydroxide precursor may include, but is not limited to, Ni. 0.6 Co 0.1 Mn 0.3 (OH)2. This application does not impose any particular restrictions on the type of lithium source, as long as it can achieve the purpose of this application. For example, the lithium source may include, but is not limited to, Li2CO3. This application does not impose any particular restrictions on the molar ratio of the hydroxide precursor and the lithium source. Those skilled in the art can select the appropriate ratio based on the chemical formula of the nickel-cobalt-manganese ternary material to be prepared, as long as it can achieve the purpose of this application. This application does not impose any particular restrictions on the amount of dopant compound added. Those skilled in the art can select the appropriate ratio based on the content of other doping and coating elements required, as long as it can achieve the purpose of this application. This application does not impose any particular restrictions on the process parameters of high-temperature sintering in step (2) above, as long as it can achieve the purpose of this application. For example, the high-temperature sintering temperature is 800℃ to 900℃, and the high-temperature sintering time is 10h to 14h.

[0044] The present application has no particular limitation on the positive current collector, as long as the purpose of the present application can be achieved. For example, the positive current collector may comprise aluminum foil, aluminum alloy foil, or the like. In the present application, there is no particular limitation on the thickness of the positive current collector and the positive active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is from 5 µm to 20 µm. The thickness of a single-layer positive active material layer is 30 µm to 120 µm. Optionally, the positive active material layer may further comprise at least one of a positive conductive agent or a positive binder. The present application has no particular limitation on the types of the positive conductive agent and the positive binder in the positive active material layer, as long as the purpose of the present application can be achieved. The present application has no particular limitation on the mass ratio of the positive active material, the positive conductive agent and the positive binder in the positive active material layer, which can be selected by those skilled in the art according to actual needs, as long as the purpose of the present application can be achieved. For example, the mass ratio of the positive active material, the positive conductive agent and the positive binder in the positive active material layer is (94~97.9): (0.8~3): (1.0~3).

[0045] In one embodiment of the present application, the secondary battery further comprises a negative electrode plate. The present application has no particular limitation on the negative electrode plate, as long as the purpose of the present application can be achieved. In one embodiment, the negative electrode plate comprises a negative current collector and a negative active material layer, the negative active material layer is disposed on one surface or both surfaces of the negative current collector, and the above-mentioned "surface" may be a partial surface of the negative current collector, or may be the entire surface of the negative current collector. The present application has no particular limitation on the negative current collector, as long as the purpose of the present application can be achieved. For example, the negative current collector may comprise copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or the like. The negative active material layer of the present application comprises a negative active material. The present application has no particular limitation on the type of the negative active material, as long as the purpose of the present application can be achieved. For example, the negative active material may comprise natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, SiO x (0<x<2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate Li4Ti5O with spinel structure 12The negative electrode material contains at least one of Li-Al alloy or metallic lithium. In this application, there are no particular limitations on the thickness of the negative electrode current collector or the negative electrode active material layer, as long as the purpose of this application is achieved. For example, the thickness of the negative electrode current collector is 6 μm to 10 μm, and the thickness of the negative electrode active material layer is 30 μm to 130 μm. Optionally, the negative electrode active material layer may further include at least one of a negative electrode conductive agent, a thickener, or a negative electrode binder. This application does not particularly limit the types of negative electrode conductive agents, thickeners, and negative electrode binders in the negative electrode active material layer, as long as the purpose of this application is achieved. This application does not particularly limit the mass ratio of the negative electrode active material, negative electrode conductive agent, thickener, and negative electrode binder in the negative electrode active material layer, as long as the purpose of this application is achieved. For example, the mass ratio of the negative electrode active material, negative electrode conductive agent, thickener, and negative electrode binder in the negative electrode active material layer is (95–98):(0–1.5):(0–3.0):(1.0–2.0).

[0046] In one embodiment of this application, the secondary battery further includes a separator disposed between the positive electrode and the negative electrode. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane. This application does not impose any particular limitation on the separator thickness, as long as it achieves the purpose of this application.

[0047] In one embodiment of this application, the secondary battery further includes a packaging bag, in which the positive electrode, negative electrode, separator, and electrolyte are contained. This application does not impose any particular limitation on the type of packaging bag, as long as it achieves the purpose of this application.

[0048] The secondary battery described in this application is not particularly limited and may include any device in which an electrochemical reaction occurs. For example, a secondary battery may include, but is not limited to, a lithium metal secondary battery, a lithium-ion secondary battery (lithium-ion battery), a lithium polymer secondary battery, or a lithium-ion polymer secondary battery.

[0049] This application does not impose any particular limitation on the preparation method of the secondary battery. Any preparation method known in the art can be used, as long as it can achieve the purpose of this application. For example, the preparation method of the secondary battery includes, but is not limited to, the following steps: stacking the separator, positive electrode, separator and negative electrode in sequence, and winding, folding or other operations as needed to obtain a wound electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the separator, positive electrode, separator and negative electrode in sequence, and then fixing the four corners of the entire stacked structure to obtain a stacked electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery.

[0050] A second aspect of this application provides an electronic device comprising the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device exhibits good performance.

[0051] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to: laptop computers, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, household large-capacity batteries, and lithium-ion capacitors.

[0052] Example

[0053] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below.

[0054] Test methods and equipment:

[0055] Particle size testing:

[0056] The particle sizes Dv10 and Dv90 of the positive electrode active material were determined using a laser particle size analyzer.

[0057] Testing of elemental content in nickel-cobalt-manganese ternary materials:

[0058] After discharging the lithium-ion battery to 3.0V at 0.5C, the positive electrode sheet is obtained. It is then cleaned by soaking in high-purity anhydrous DMC for 8 hours. After cleaning three times, it is left to stand in a vacuum drying oven for 12 hours. The material of the positive active material layer is scraped off from the positive electrode sheet and then tested by inductively coupled plasma optical emission spectrometry (ICP) to obtain the content of each element in the nickel-cobalt-manganese ternary material.

[0059] Capacity decay consistency test after storage at 60℃:

[0060] The lithium-ion battery was placed at 25°C and charged at a constant current of 0.5C to 4.4V. Then, it was charged at a constant voltage of 4.4V to a current of 0.05C. After resting for 5 minutes, it was discharged at a constant current of 0.5C to 3.0V. This is the initial discharge capacity Q1. The lithium-ion battery was then charged at a constant current of 0.5C to 4.4V again, and then charged at a constant voltage of 4.4V to a current of 0.05C. The lithium-ion battery was placed in a 60°C high-temperature furnace and left to stand for 35 days. After 35 days, it was removed and placed at 25°C, and discharged at a constant current of 0.5C to 3.0V. This is the remaining discharge capacity Q2.

[0061] Capacity retention rate (%) = (Q2 / Q1) × 100%.

[0062] Fifteen lithium-ion batteries were tested using the same method, and the capacity retention rate was calculated using the same method. Then, the standard deviation of the capacity retention rate of the 15 batteries was calculated. The larger the standard deviation, the worse the consistency of capacity decay; the smaller the standard deviation, the better the consistency of capacity decay.

[0063] Example 1-1

[0064] <Preparation of Electrolyte>

[0065] In an argon-atmospheric glove box with a water content <10 ppm, ethylene carbonate, propylene carbonate, and diethyl carbonate were mixed in a 1:1:2 ratio to obtain an organic solvent. Then, a nitrile compound (succinate), a sulfur-oxygen double bond compound (1,3-propanesulfonate lactone), and a lithium salt compound (lithium hexafluorophosphate (LiPF6)) were added to the organic solvent, and the mixture was stirred until homogeneous to obtain an electrolyte. The mass percentage W of the sulfur-oxygen double bond compound is based on the mass of the electrolyte. 11 =2.5%, mass percentage of nitrile compounds W 12 =1%, the mass percentage of lithium salt is 12%, and the balance is organic solvent.

[0066] <Preparation of the positive electrode>

[0067] The positive electrode active material is a nickel-cobalt-manganese ternary material (LiNi). 0.6 Co 0.1 Mn 0.3O2), positive electrode conductive agent acetylene black, positive electrode binder polyvinylidene fluoride (PVDF, weight average molecular weight 5×10⁻⁶), and positive electrode binder polyvinylidene fluoride (PVDF, weight average molecular weight 5×10⁻⁶). 5 The materials were mixed at a mass ratio of 94:3:3, with N-methylpyrrolidone (NMP) added as a solvent. The mixture was stirred under vacuum until a homogeneous positive electrode slurry with a solid content of 75 wt% was obtained. The positive electrode slurry was uniformly coated onto one surface of a 6 μm thick aluminum foil current collector and dried at 90°C to obtain a positive electrode sheet with a single-sided coating of positive active material (80 μm thick). The above steps were then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating of positive active material. After cold pressing and slitting, positive electrode sheets with dimensions of 74 mm × 851 mm were obtained for later use. The particle size of the positive active material was Dv10 (D1 = 1.4 μm) and Dv90 (D2 = 5 μm). Based on the total mass of nickel, cobalt, and manganese, the molar percentage of nickel was M3 = 60%, and the mass percentage of other doped elements was W4 = 0%.

[0068] <Preparation of Negative Electrode Sheets>

[0069] Artificial graphite as the negative electrode active material and styrene-butadiene rubber (SBR) as the negative electrode binder (weight average molecular weight 5×10⁻⁶) are used. 6 Thickener sodium carboxymethyl cellulose was mixed at a mass ratio of 95:2:3, deionized water was added, and the mixture was stirred evenly under vacuum to obtain a negative electrode slurry with a solid content of 75 wt%. The negative electrode slurry was uniformly coated onto one surface of a 5 μm thick copper foil current collector. The copper foil was dried at 85°C for 4 hours to obtain a negative electrode sheet with a single-sided negative electrode material layer. The above steps were repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer. After cold pressing, cutting, and slitting, a negative electrode sheet with a size of 76.6 mm × 875 mm was obtained. The coating weight of the negative electrode material layer was D = 0.15 g / 1540.25 mm. 2 The average particle size of the negative electrode active material is Dv50 = 11 μm.

[0070] <Preparation of the diaphragm>

[0071] The adhesive PVDF (weight average molecular weight of 5×10) 5Inorganic alumina particles were mixed at a mass ratio of 1:2, and NMP was added as a solvent to prepare an inorganic layer slurry with a solid content of 12 wt%. The slurry was stirred evenly and then uniformly coated onto one surface of a 5 μm thick polyethylene substrate. The substrate was then dried at 85°C for 4 hours to obtain a diaphragm with a single-sided inorganic layer coating thickness of 2 μm. PVDF was then added to NMP solvent and stirred evenly to prepare a polymer layer slurry with a solid content of 25 wt%. This polymer layer slurry was then uniformly coated onto the surface of the inorganic layer, with a surface density of 0.15 mg / cm³. 2 Then, it is dried at 85℃ for 4 hours. Finally, a polymer layer slurry is uniformly coated on the other surface of the polyethylene substrate. The areal density of the polymer layer slurry is 0.15 mg / cm³. 2 Then, it is dried at 85°C for 4 hours to obtain a diaphragm with an inorganic layer and a polymer layer on one side and only a polymer layer on the other side.

[0072] <Preparation of Lithium-ion Batteries>

[0073] The separator, negative electrode, and positive electrode prepared above are stacked and wound in sequence to obtain a wound electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, degassing, and edge trimming, a lithium-ion battery is obtained. Formation steps: constant current charging at 0.02C to 3.3V, and then constant current charging at 0.1C to 3.6V.

[0074] Examples 1-2 to 1-22

[0075] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1.

[0076] In Examples 1-13 to 1-22, when the mass percentage of nitrile compounds and / or sulfur-oxygen double bond compounds changes, the mass percentage of organic solvent changes accordingly, and the sum of the mass percentages of organic solvent, nitrile compounds and sulfur-oxygen double bond compounds is 100%.

[0077] Examples 2-1 to 2-4

[0078] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as in Examples 1-1.

[0079] Examples 3-1 to 3-3

[0080] Except for adjusting the type of positive electrode active material and the change in the molar content ratio of nickel according to Table 3, the rest is the same as in Example 1-1.

[0081] Examples 3-4

[0082] <Preparation of Positive Electrode Active Materials>

[0083] According to the chemical formula LiNi 0.6 Co 0.1 Mn 0.3 O2 will react with the hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 After thoroughly mixing (OH)₂ and Li₂CO₃ (Li:transition metal molar ratio of 1.05, transition metals being Ni, Co, and Mn), Al₂O₃ is added and mixed evenly to obtain a mixture in which the total mass ratio of Al to Ni, Co, and Mn is 5:100. The resulting mixture is then placed in a tube furnace under a pure oxygen atmosphere at 500°C for 6 hours, heated to 850°C at a rate of 5°C / min and held for 12 hours. After cooling to room temperature, it is removed and ground to obtain LiNi doped with 5% Al. 0.6 Co 0.1 Mn 0.3 O2 powder sample. Except for adjusting the type of positive electrode active material to the positive electrode active material prepared above, it is the same as in Example 1-1.

[0084] Examples 3-5

[0085] <Preparation of Positive Electrode Active Materials>

[0086] According to the chemical formula LiNi 0.6 Co 0.1 Mn 0.3 O2 will react with the hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 After thoroughly mixing (OH)₂ and Li₂CO₃ (Li:transition metal molar ratio of 1.05, transition metals being Ni, Co, and Mn), ZrO₂ and TiO₂ are added and mixed evenly to obtain a mixture, wherein the total mass ratio of Zr, Ti to Ni, Co, and Mn is 2:100 and 3:100, respectively. The resulting mixture is then placed in a tube furnace under a pure oxygen atmosphere at 500℃ for 6 hours, heated to 850℃ at a rate of 5℃ / min and held for 12 hours, and then cooled to room temperature before being ground to obtain LiNi containing 2% Zr doping and 3% Ti doping. 0.6 Co 0.1 Mn 0.3 O2 powder sample. Except for adjusting the type of positive electrode active material to the positive electrode active material prepared above, it is the same as in Example 1-1.

[0087] Examples 3-6

[0088] <Preparation of Positive Electrode Active Materials>

[0089] According to the chemical formula LiNi 0.6 Co 0.1 Mn 0.3 O2 will react with the hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 After thoroughly mixing (OH)₂ and Li₂CO₃ (Li:transition metal molar ratio of 1.05, transition metals being Ni, Co, and Mn), Al₂O₃ is added and mixed evenly to obtain a mixture in which the total mass ratio of Al to Ni, Co, and Mn is 1:100. The resulting mixture is then placed in a tube furnace under a pure oxygen atmosphere at 500°C for 6 hours, heated to 850°C at a rate of 5°C / min and held for 12 hours. After cooling to room temperature, it is removed and ground to obtain LiNi doped with 1% Al. 0.6 Co 0.1 Mn 0.3 O2 powder sample. Except for adjusting the type of positive electrode active material to the positive electrode active material prepared above, it is the same as in Example 1-1.

[0090] Examples 3-7

[0091] <Preparation of Positive Electrode Active Materials>

[0092] According to the chemical formula LiNi 0.6 Co 0.1 Mn 0.3 O2 will react with the hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 After thoroughly mixing (OH)₂ and Li₂CO₃ (Li:transition metal molar ratio of 1.05, transition metals being Ni, Co, and Mn), Al₂O₃ is added and mixed evenly to obtain a mixture in which the total mass ratio of Al to Ni, Co, and Mn is 9:100. The resulting mixture is then placed in a tube furnace under a pure oxygen atmosphere at 500°C for 6 hours, heated to 850°C at a rate of 5°C / min and held for 12 hours. After cooling to room temperature, it is removed and ground to obtain LiNi doped with 9% Al. 0.6 Co 0.1 Mn 0.3 O2 powder sample. Except for adjusting the type of positive electrode active material to the positive electrode active material prepared above, it is the same as in Example 1-1.

[0093] Examples 3-8

[0094] <Preparation of Positive Electrode Active Materials>

[0095] According to the chemical formula LiNi 0.6 Co 0.1 Mn0.3 O2 will react with the hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 After thoroughly mixing (OH)₂ and Li₂CO₃ (Li:transition metal molar ratio of 1.05, transition metals being Ni, Co, and Mn), Al₂O₃ is added and mixed evenly to obtain a mixture in which the total mass ratio of Al to Ni, Co, and Mn is 11:100. The resulting mixture is then placed in a tube furnace under a pure oxygen atmosphere at 500°C for 6 hours, heated to 850°C at a rate of 5°C / min and held for 12 hours. After cooling to room temperature, it is removed and ground to obtain LiNi doped with 11% Al. 0.6 Co 0.1 Mn 0.3 O2 powder sample. Except for adjusting the type of positive electrode active material to the positive electrode active material prepared above, it is the same as in Example 1-1.

[0096] Comparative Examples 1 to 8

[0097] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1.

[0098] When the mass percentage of nitrile compounds and / or sulfur-oxygen double bond compounds changes, the mass percentage of organic solvents also changes accordingly. The sum of the mass percentages of organic solvents, nitrile compounds, and sulfur-oxygen double bond compounds is 100%.

[0099] The preparation and performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.

[0100] Table 1

[0101] As can be seen from Examples 1-1 to 1-22 and Comparative Examples 1 to 8, the secondary batteries in the embodiments of this application, by adjusting D2 / D1, D2, W1, and D2×W1 to be within the scope of this application, achieve a larger standard deviation of capacity retention, indicating that the capacity consistency between different cells in the secondary battery is improved. In contrast, the secondary batteries in the comparative examples, where at least one of D2 / D1, D2, W1, or D2×W1 is not within the scope of this application, have a smaller standard deviation of capacity retention, indicating poorer capacity consistency between different cells in the comparative secondary batteries.

[0102] D2 / D1, D2, and D1 typically affect the standard deviation of capacity retention in secondary batteries. As can be seen from Examples 1-1 to 1-13 and Comparative Examples 1 to 4, secondary batteries using D2 / D1, D2, and D1 within the scope of this application exhibit a larger standard deviation of capacity retention, indicating a higher consistency in capacity among different cells of the secondary battery.

[0103] W1 and D2×W1 typically affect the standard deviation of capacity retention in secondary batteries. As can be seen from Examples 1-4, Examples 1-14 to Examples 1-22, and Comparative Examples 5 to 8, secondary batteries using W1 and D2×W1 within the scope of this application exhibit a larger standard deviation of capacity retention, indicating a higher capacity consistency among different cells in the secondary battery.

[0104] mass percentage of sulfur-oxygen double bond compounds W 11 This typically affects the standard deviation of the capacity retention rate of secondary batteries. As can be seen from Examples 1-4, 1-14 to 1-20, the mass percentage W of the selected sulfur-oxygen double bond compound... 11 The secondary batteries within the scope of this application have a large standard deviation of capacity retention, indicating that the capacity consistency among different cells in the secondary battery is high.

[0105] mass percentage of nitrile compounds W 12 This typically affects the standard deviation of the capacity retention rate of secondary batteries. As can be seen from Examples 1-4, 1-14 to 1-18, 1-21, and 1-22, the mass percentage W of the selected nitrile compound... 12 The secondary batteries within the scope of this application have a large standard deviation of capacity retention, indicating that the capacity consistency among different cells in the secondary battery is high.

[0106] Table 2

[0107] The types of sulfur-oxygen double bond compounds and nitrile compounds typically affect the standard deviation of capacity retention in secondary batteries. As can be seen from Examples 1-1, 2-1 to 2-4, secondary batteries using sulfur-oxygen double bond compounds and nitrile compounds within the scope of this application exhibit a larger standard deviation of capacity retention, indicating a higher capacity consistency among different cells in the secondary battery.

[0108] Table 3 Note: In Table 3, "\" indicates that there is no corresponding parameter.

[0109] The nickel content of the positive electrode active material typically affects the cycle life of a secondary battery. As can be seen from Examples 1-1, 3-1 to 3-3, secondary batteries using positive electrode active materials with nickel content within the range of this application exhibit a larger standard deviation of capacity retention, indicating a higher capacity consistency among different cells in the secondary battery.

[0110] When the positive electrode active material includes other doped coating elements, the type and content of these other doped coating elements usually affect the cycle life of the secondary battery. As can be seen from Examples 1-1, 3-4 to 3-8, secondary batteries using other doped coating elements within the scope of this application have a larger standard deviation of capacity retention, indicating a higher capacity consistency among different cells in the secondary battery.

[0111] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.

[0112] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.

[0113] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A secondary battery, comprising a positive electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising a positive active material, wherein the particle size Dv10 of the positive active material is D1μm, the particle size Dv90 of the positive active material is D2μm, 1.2≤D2 / D1≤6.6, 2.9≤D2≤7.8; The electrolyte includes at least one of a sulfur-oxygen double bond compound or a nitrile compound, and the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is W1% based on the mass of the electrolyte, where 0.5 ≤ W1 ≤ 7. D2 and W1 satisfy: 1.5≤D2×W1≤30.

2. The secondary battery according to claim 1, wherein, 0.9≤D1≤4.8。 3. The secondary battery according to claim 1 or 2, wherein, The secondary battery satisfies at least one of the following characteristics: (1) 2≤D2 / D1≤5; (2)3.5≤D2≤7; (3)2≤W1≤6; (4) 8 ≤ D2 × W1 ≤ 25; (5)1≤D1≤3。 4. The secondary battery according to claim 1, wherein, Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is W. 11 The mass percentage of the nitrile compound is W. 12 %, 0.5≤W 11 ≤6, 0.1≤W 12 ≤3.

5. The secondary battery according to claim 4, wherein, The secondary battery satisfies at least one of the following characteristics: (i)1.5≤W 11 ≤4.2; (ii)0.3≤W 12 ≤2.1。 6. The secondary battery according to claim 1, wherein, The sulfur-oxygen double bond compound includes at least one of 1,3-propanesulfonate, vinyl sulfate, propenesulfonate lactone, 3-fluoro-1,3-propanesulfonate lactone, 1,2-propanesulfonate lactone, 1,4-butanesulfonate lactone, 1,2-butanesulfonate lactone, 1,3-butanesulfonate lactone, 2,4-butanesulfonate lactone, or 1,3-pentanesulfonate lactone.

7. The secondary battery according to claim 1, wherein, The nitrile compounds include at least one of malononitrile, butadionitrile, glutaronitrile, adiponitrile, heptanonitrile, octadionitrile, 3,3'-oxadipropionitrile, hex-2-enadionitrile, trans-butenedionitrile, 2-pentenedionitrile, methylglutaronitrile, 4-cyanohepanitrile, (Z)-but-2-enadionitrile, 2,2,3,3-tetrafluorobutadionitrile, ethylene glycol bis(propionitrile) ether, 4-cyanohepanitrile, 4-(2-cyanoethyl)heptanedionitrile or 1,2,3-tris-(2-cyanoethoxy)propane, 1,4-dicyano-2-butene, 1,3,6-hexanetrionitrile or 1,2,3-tris(2-cyanoxy)propane.

8. The secondary battery according to claim 1, wherein, The sulfur-oxygen double bond compound includes at least one of 1,3-propanesulfonyl lactone, propenesulfonyl lactone, or 2,4-butanesulfonyl lactone; and / or, the nitrile compound includes at least one of adiponitrile, succinic acid, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrionitrile, or 1,2,3-tris(2-cyanoxy)propane or 1,4-dicyano-2-butene.

9. The secondary battery according to claim 1, wherein, The positive electrode active material is a nickel-cobalt-manganese ternary material. Based on the total molar amount of the three elements, nickel, cobalt, and manganese, the molar content of nickel is M3%, and M3≥50. The positive electrode active material also includes other doping coating elements, which include at least one of Al, Ta, Zr, B, Ti or Y. Based on the total mass of the nickel-cobalt-manganese ternary material, the mass percentage of the other doping coating elements is W4%, where 0 ≤ W4 < 10.

10. An electronic device, wherein, The electronic device includes a secondary battery as described in any one of claims 1 to 9.